Analisis Elektrifikasi Transportasi Untuk Penghematan Subsidi BBM - Fitrah, Habib; Marliyah, Marliyah; Bi Rahmani, Nur Ahmadi (Jurnal Ilmiah Ekonomi Islam, 2024)
The purpose of this study is to measure how much electric vehicles have an impact on state budget savings on fuel subsidies in Indonesia, This study uses a quantitative method of a simple linear regression model in this study using data on electric vehicles and fuel subsidies from 2020-2022 with data sources from Katadata, from the results of this study there are results that have a positive effect on electric vehicles on state budget savings, with an influence of 93%. Because electric vehicles do not need to be subsidized because the charging cost is very cheap, and the budget from this fuel subsidy can be diverted to fundamental things, such as the progress of Infrastructure, Education and Health. And the per capita income of the Indonesian people will increase because their expenses for commuting are saved by 70 percent by using electric vehicles.